The Significance of Preoperative Neutrophil to Lymphocyte Ratio in Patients with Meningiomas - Özdemir, Ahmet Faruk; Kaçıra, Tibet; Kemerdere, Rahşan; Tanrıverdi, Taner (Cerrahpaşa Medical Journal, 2022)
Objective: This study aims to evaluate the significance of preoperative neutrophil to lymphocyte and platelet to lymphocyte ratios in predicting the pathological grade of supratentorial meningiomas. Methods: This retrospective study included a total of 94 patients with newly diagnosed supratentorial meningiomas. Preoperative lymphocyte, neutrophil, platelet counts, and neutrophil to lymphocyte and platelet to lymphocyte ratios were obtained. Results: Of the 94 patients, 73 patients and 21 patients showed low- and high-grade meningiomas, respectively. Among the hematological markers, only neutrophil to lymphocyte ratio showed significantly higher value in high-grade meningioma group and showed diagnostic efficacy in predicting the pathological grade. Conclusions: The higher the neutrophil to lymphocyte ratio, the higher the grade of meningioma. This can help neurosurgeons to have better treatment plan before the surgical intervention. Cite this article as: Özdemir AF, Kaçıra T, Kemerdere R, Tanrıverdi T. The significance of preoperative neutrophil to lymphocyte ratio in patients with meningiomas. Cerrahpaşa Med J. 2022;46(3):245-248.